1990
DOI: 10.1159/000168126
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Adenosine Calcium and Ischemia in Radiocontrast-Induced Intrarenal Vasoconstriction

Abstract: These studies were designed to test the hypothesis that adenosine and calcium are important in mediating radiocontrast-media-associated reduction in renal blood flow (RBF) in the dog. Intravenous verapamil (V) and diltiazem (DTZ) infusion significantly attenuated the magnitude of the vasoconstrictor response observed after each intrarenal contrast media (CM) injection. (First injection: -47 ± 8% control vs. -14 ± 3% V, p < 0.03; -38 ± 4% control vs. -19 ± 3% DTZ, p < 0.02. Second injection: -33 ± 6% control vs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(38 citation statements)
references
References 7 publications
(10 reference statements)
1
36
0
1
Order By: Relevance
“…Gouyon et al [14] demonstrated in newborn and adult animals that the fall in glomerular filtration induced by hypoxemia can be prevented by theophylline in low doses. Used commonly for apnea of prematurity, theophylline has also been shown to prevent both the reduction of GFR after contrast media application in humans and the renal insufficiency induced by hypoxemia in newborns with respiratory distress syndrome [17,18,19]. Similar results were reported in human adults with chronic renal insufficiency [20].…”
Section: Discussionsupporting
confidence: 53%
“…Gouyon et al [14] demonstrated in newborn and adult animals that the fall in glomerular filtration induced by hypoxemia can be prevented by theophylline in low doses. Used commonly for apnea of prematurity, theophylline has also been shown to prevent both the reduction of GFR after contrast media application in humans and the renal insufficiency induced by hypoxemia in newborns with respiratory distress syndrome [17,18,19]. Similar results were reported in human adults with chronic renal insufficiency [20].…”
Section: Discussionsupporting
confidence: 53%
“…In vitr o and animal studies sug g est that damag e secondary to iodinated contrast to the kidneys is likely mediated by a combination of toxic or obstructive injury to the renal tubules, ischemic injury by reactive oxygen species, and renal medullary hypoxia. The predominant factor is likely to be renal medullary hypoxia, in which adenosine, calcium, and endothelin bring about intrarenal vasoconstriction after contrast exposure [17,[20][21][22][23][24][25] . Tubular toxicity is also thought to play a role in CIN through both direct nephrotoxicity and tubular obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…The calcium channel blockers have been suggested as beneficial in the prevention of CIN. Theoretically, their administration may block the renal vasoconstriction induced by contrast and reduce the nephrotoxic effect and this has been demonstrated in an animal model [40,41]. Rodicio et al [42] have reported that diltiazem will reduce the nephrotoxic effect of contrast and may allow faster renal recovery.…”
Section: Prevention Of Contrast-induced-nephropathymentioning
confidence: 99%